A new Puccinia on endemic Phryna - Hüseyin, E; Kirbag, S (Pakistan Botanical Soc, 2003)
The rust fungus Puccinia phrynae sp. nov. is described and illustrated from endemic Phryna ortegioides collected in East Anatolia, Turkey.